WORKER HEALTH: STUDY ASSOCIATIVE BETWEEN WORK SHIFT AND PREVALENCE OF DISEASE (Fiep Bulletin - online, 2013)
The workday is directly connected with the welfare of the worker as well with the emergence of diseases caused by overwork. The present study aimed to investigate the association between working hours of teachers in a public HEI state of Paraná and involvement by evils arising from routine work. Study participants were 146 teachers who responded to the workday and diseases, BMI was also calculated and categorized as previously described. There were no significant associations between workload and prevalence of diseases or between working hours and BMI. Thus it is suggested that further studies be conducted to investigate other variables as well that the teacher is of paramount importance to the institution.
Keywords: working hours; diseases and BMI